إلقاء السلام ورده في الصلاة (دراسة حديثية) - Muthahhir Anshar Lamiry (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research raises the subject of discussion regarding marfuk hadiths regarding the issue of giving and responding to greetings in prayer, which are collected in al-Kutub al-Sittah. The aim of this research is to find out the hadiths related to giving and responding to greetings in prayer, to find out the degree of these hadiths in terms of their validity and authenticity, as well as an explanation regarding the jurisprudential rules of giving and answering greetings in prayer. The methods used in this research are inductive and analytical. Among the conclusions are, first, that there are six hadiths on this issue from al-Kutub al-Sittah. Second, four of the hadiths are authentic, namely: the hadith of Abdullāh bin Mas'ūd, the hadith of Jābir bin 'Abdillāh, the hadith of Ṣuhaib bin Sinān, and the hadith of Abu Hurairah. As for the hadith of Bilāl bin Rabāḥ and the hadith of Ammār bin Yāsir, there are weaknesses in their sanad. Third, these hadiths show the ability to greet people who pray based on the iqrar of the Prophet Ṣallallāhu 'alaihi wa sallam. It is prescribed to answer greetings in prayer by gesturing with the palm of the hand or fingers. As for answering greetings with lafaz, this is included in the words that are prohibited in prayer.